2006
DOI: 10.1002/chem.200500885
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Intercalators and Avidin Probes Derived from Luminescent Cyclometalated Iridium(III)–Dipyridoquinoxaline and –Dipyridophenazine Complexes

Abstract: Six luminescent cyclometalated iridium(III)-dipyridoquinoxaline and -dipyridophenazine complexes [Ir(ppy)2(N-N)](PF6) (Hppy = 2-phenylpyridine; N-N = dipyrido[3,2-f:2',3'-h]quinoxaline, dpq (1); 2-n-butylamidodipyrido[3,2-f:2',3'-h]quinoxaline, dpqa (2); 2-((2-biotinamido)ethyl)amidodipyrido[3,2-f:2',3'-h]quinoxaline, dpqB (3); dipyrido[3,2-a:2',3'-c]phenazine, dppz (4); benzo[i]dipyrido[3,2-a:2',3'-c]phenazine, dppn (5); 11-((2-biotinamido)ethyl)amidodipyrido[3,2-a:2',3'-c]phenazine, dppzB (6)) have been desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(86 citation statements)
references
References 116 publications
6
80
0
Order By: Relevance
“…The coordination geometry of iridium is similar to that found in previously studied diaminobis(phenylpyridine)iridiumA C H T U N G T R E N N U N G (III) type cations, where the diamino ligands were various bipyridine derivatives [8c, e, 19, 20] and dipyrido[3,2-a:2',3'-c]phenazine (dppz). [21] To our knowledge, no 1,10-phenanthroline complex of this type has been characterised crystallographically. The Ir atom in 18 adopts a distorted octahedral coordination.…”
Section: Wwwchemeurjorgmentioning
confidence: 98%
“…The coordination geometry of iridium is similar to that found in previously studied diaminobis(phenylpyridine)iridiumA C H T U N G T R E N N U N G (III) type cations, where the diamino ligands were various bipyridine derivatives [8c, e, 19, 20] and dipyrido[3,2-a:2',3'-c]phenazine (dppz). [21] To our knowledge, no 1,10-phenanthroline complex of this type has been characterised crystallographically. The Ir atom in 18 adopts a distorted octahedral coordination.…”
Section: Wwwchemeurjorgmentioning
confidence: 98%
“…[5][6][7]30] This is also caused by steric effects, which modulate DNA binding. Clearly, if L 1 of 4 slots into the narrow minor groove, the octahedral coordination geometry of the complex means that the bulky and elongated dppz ligand will project into the groove wall, which would produce large www.chemeurj.org unfavorable steric interactions.…”
Section: Compared With 1 2 and 3 Complex 4 Displays A Very Differementioning
confidence: 99%
“…[6] This work has also been extended to other d 6 metal ions, with the binding properties of dppz complexes based on Re I , Os II , and Ir III centers all having been described. [7] Related homo-and heterometallic dinuclear intercalators are also known. [8] In contrast, much less work on metal complexes capable of groove binding has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the most conventional and commonly used organic dyes, transitionmetal-complex dyes represent an attractive family of luminescent materials for life science research, because they display many superior physicochemical properties, such as higher photostabilities, larger Stokes shifts, and higher quantum efficiencies. [1] For example, recent studies on luminescent iridiumA C H T U N G T R E N N U N G (III) complexes have found emerging grounds for applications of these dyes in chemosensors, [2] biolabeling, [3,4] live cell staining, [5][6][7][8][9] and in vivo tumor imaging. [10] Secondly, the choice of conjugation chemistry is also important to consider.…”
mentioning
confidence: 98%